Some ℓ(p)-Type New Sequence Spaces and Their Geometric Properties - Ekrem Savaş; Vatan Karakaya; Necip Şimşek (Abstract and Applied Analysis)
We introduce an ℓ(p)-type new sequence space and investigate its some topological properties including AK and AD properties. Besides, we examine some geometric properties of this space concerning Banach-Saks type p and Gurarii's modulus of convexity.